An Analysis of Slaveholders According to the 1850 Census - Barry R. Chiswick; RaeAnn Halenda Robinson (Institute of Labor Economics (IZA), 2025)
This paper analyzes the characteristics of the free population who were recorded as "owners" of enslaved people in the antebellum Southern states. We utilize the first nationally representative sample linking enslaved and free people - the 1/100 sample microdata files of the 1850 Census of Population from Schedule 1 on free people, and Schedule 2 on the enslaved population - to identify the slaveholders and their slaveholdings. The reduced form regression analyses consider both owning at least one enslaved person, and among slaveholders the number held. The findings indicate that 90 percent of the enslaved population were reportedly held by free males, that among men this was more likely for those who were married, but among women it was lower for the married, that for both genders slaveholding increased with age, being literate, and having been born in the US. Moreover, it varied by free men's occupation, in part because of the extent of self-employment and in part due to their wealth. While most slaveholders were self-employed farmers, many of the slaveholders were professionals, including clergy, doctors, and lawyers who used enslaved people in their household, in their professional practice, or in the farms/plantations that they also owned.
Keywords: N10; N9; N31; 330; enslaved people; slaveholders; 1850 census of population; schedule 2 – slave inhabitants; occupations; gender; literacy; nativity